Effect of Chinese Medicine Xinmaitong on Blood Pressure in Spontaneously Hypertensive Rats - Zhang, Bin (Cardiol Res Pract, 2020)
OBJECTIVE: To investigate the effect of traditional Chinese antihypertensive compound Xinmaitong on blood pressure and vasoactive factors of vasoconstrictor endothelin-1 (ET-1) and vasodilator calcitonin gene related peptide (CGRP) in spontaneously hypertensive rats (SHRs) with early stage hypertension. METHODS: Twenty male SHRs were randomly divided into two groups: 10 for hypertensive control group and 10 for hypertensive treatment group. In addition, 10 Wistar rats were used as the normal control group without any intervention. SHRs of hypertensive treatment group were orally treated with Xinmaitong, while the hypertensive control group was treated with the normal saline (NS) for a total of eight weeks. The blood pressure in SHRs was examined before and after the end of the eight-week study. After treatment, the rats were killed and the blood samples were collected to measure plasma levels of ET-1 and CGRP by ELISA method, respectively. Meanwhile, the aorta rings were isolated for measuring the mRNA expression of ET-1 and CGRP by PCR. Moreover, the protein levels of ET-1 and CGRP were studied by immunohistochemical. RESULTS: Daily oral administration of Xinmaitong resulted in significant fall in the SHRs' blood pressure, including systolic and diastolic blood pressures (SBP and DBP), mean blood pressure (MBP), and pulse pressure (PP). The plasma ET-1 levels were reduced and CGRP increased. In parallel, the mRNA and protein expression of ET-1 were decreased, whereas the mRNA and protein expression of CGRP were enhanced in SHRs treated with Xinmaitong. CONCLUSION: The present study demonstrated for the first time that Xinmaitong leads to the fall in blood pressure of SHRs and that this antihypertensive effect is, at least in part, due to improvement of arterial tone.